Blogosphere: How Youth Perceived Blogs Credibility - Noor Azlin, Bidin; Normah, Mustaffa (2012)
Malaysia practice open democracy and would continue to promote digital democracy as Internet is an engine for economic growth and a portal to a knowledge society. Malaysia which has set its sights on becoming a high-income nation in nine years had one of the liveliest and least controlled blogosphere in the world. Bloggers are not only limited to adult political specialists or amateur journalists, but also in the world of youths, where blogs offer an outlet for personal expressions and reflection, as well as way to communicate and connect with others. The overabundance of information available online, coupled with the heavy reliance on the Internet by information-seekers raises the issue of the credibility or quality of blogs found online. Questions and concerns about credibility stems from the fact that Internet and digitization technologies have lowered the cost of information dissemination while increasing the accessibility to information. Using quantitative approach, this paper aims to present some findings in relation to the youth’s perception on the credibility of blogs. Considering the wide usage of blogs and its influences among Malaysian Internet users, these surveys while by no means comprehensive, gives a preliminary idea of the dynamism of the blogosphere in Malaysia and may explain how to assess the credibility of online information.